A systematic scoping review of diagnostic validity in avoidant/restrictive food intake disorder. Issue 4 (29th November 2018) - Strand, Mattias; von Hausswolff‐Juhlin, Yvonne; Welch, Elisabeth
Abstract: Objective: Avoidant/restrictive food intake disorder (ARFID) was introduced as a new diagnosis in the DSM‐5. This systematic scoping review explores how ARFID as a diagnostic entity is conceptualized in the research literature and evaluates the diagnostic validity according to the Feighner criteria. Method: A systematic scoping review of papers on ARFID in PubMed/MEDLINE and Web of Science was undertaken, following PRISMA and Joanna Briggs Institute guidelines. Results: Fifty‐one original research publications, 23 reviews and commentaries, and 20 case reports were identified. The use of ARFID as a conceptual category varies significantly within this literature. At this time, the ARFID diagnosis does not fulfil the Feighner criteria for evaluating the validity of diagnostic constructs, the most urgent problem being the demarcation toward other disorders. A three‐dimensional model—lack of interest in food, selectivity based on sensory sensitivity, and fear of aversive consequences—is gaining support in the research literature. Discussion: The introduction of the ARFID diagnosis has undoubtedly increased the recognition of a previously largely neglected group of patients. However, this article points to an inability of the current DSM‐5 diagnostic criteria to ensure optimal diagnostic validity, which risks making them less useful in clinical practice and in epidemiological research. To increase the conceptual validity of the ARFID construct, several possible alterations to the current diagnostic criteria are suggested, including a stronger emphasis of the three identified subdomains and further clarifying the boundaries of ARFID.